Rancang Bangun Mesin Penyerut Bahan Baku Anyaman Rotan Dengan Mekanisme Double Roll - Edilla, Edilla; Farhan, Muhammad; Rahmawaty, Made; Jaenudin, Jajang; Ma'a, Mustaza (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
Rattan Is one of the plants that grow in Indonesia, One of the areas that includes many rattan producers is Riau. Rattan is a plant that is one of the raw materials in the handicraft and furniture industry, therefore, to take advantage of the many rattan plants can be used as a furniture product such as tables, chairs and other handicrafts. The machine is designed using a driving force using a 1 phase electric motor using a double roll pulling system made of rubber and using a blade with a diameter of 5 mm, and this machine also has a safety on the control system so that the AC motor is not easily burned when the current is excessive. This machine can produce 76 rattan sticks per hour with a size 5 mm diameter and 300 cm lenght so that it can increase rattan production more effectively and efficiently. This rattan shaving machine is capable of shaving 300 cm of raw rattan with a diameter of 10-13 mm and the consistency of the thickness produced is 5 mm in diameter with an error rate of 0.22%.